2006
DOI: 10.1364/ol.31.001453
|View full text |Cite
|
Sign up to set email alerts
|

Stable coherent coupling of laser diodes by a volume Bragg grating in photothermorefractive glass

Abstract: Two separate laser diodes emitting near 980 nm were coupled by a thick volume Bragg grating recorded in a photothermorefractive glass. The coupled diodes emitted at the same wavelength with a spectral width narrowed to below the resolution of the spectrum analyzer (<30 pm). Coherent emission at a pumping level greater than five times above the threshold was observed for several months with near-unity visibility of the interference pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…High efficiency diffractive optical elements recorded in PTR glass have shown robustness under harsh conditions of utilization such as elevated temperatures and high power laser irradiation. These elements have been used for spectral beam combining [3], selection of transverse and longitudinal modes in different laser resonators [4], high brightness semiconductor lasers [5], etc. However, all of these diffractive optical elements were recorded via linear excitation of Ce 3+ (photo-sensitizer in PTR glass) within its spectrum of photosensitivity (280-350 nm).…”
Section: Introductionmentioning
confidence: 99%
“…High efficiency diffractive optical elements recorded in PTR glass have shown robustness under harsh conditions of utilization such as elevated temperatures and high power laser irradiation. These elements have been used for spectral beam combining [3], selection of transverse and longitudinal modes in different laser resonators [4], high brightness semiconductor lasers [5], etc. However, all of these diffractive optical elements were recorded via linear excitation of Ce 3+ (photo-sensitizer in PTR glass) within its spectrum of photosensitivity (280-350 nm).…”
Section: Introductionmentioning
confidence: 99%
“…VHGs recorded in glass have been first suggested for use in coherent coupling of diode lasers in Refs. [37,38]. The basic idea of this approach is to use volume Bragg gratings to create extremely dispersive external resonators for coherently combining individual lasers.…”
Section: Volume Holographic Gratingmentioning
confidence: 99%
“…The VHG is acting within this approach as a common output coupler. Venus et al [37,38] coherently coupled two 980-nm diode lasers and produced single wavelength output for both diodes with spectral width narrowed to \30 pm. Similar technology can be applied for high-power fiber lasers using coherent beam combining and is potentially capable of achieving 100-kW level of coherent fiber laser radiation.…”
Section: Volume Holographic Gratingmentioning
confidence: 99%
“…A new approach to this problem was demonstrated in publications [22,23] where extremely narrow-band PTR VBGs were used for radiation exchange between two laser diodes. It was demonstrated that coherent radiation from two laser diodes placed at separated stages could be observed for a year at driving current exceeding 4 thresholds.…”
Section: Phase Locking In Multi-channel Resonatorsmentioning
confidence: 99%